Feasibility Analysis Of The Malaga Beach Tourism Object In Siwalu Banua Ii Village Gunungsitoli Idanoi Distrct Gunungsitoli City North Sumatra - Gea, Rosmawati; Gulo, Martin; Dawolo, Januari; Telaumbanua, Betzy Victor; Laoli, Destriman; Zebua, Ratna Dewi (Jurnal Ilmu Pertanian dan Perikanan, 2024)
This research was conducted at Malaga Beach, Siwalu Banua II Village, Gunungsitoli Idanoi District, Gunungsitoli City, North Sumatra Province, with the aim of determining the feasibility of beach tourism objects from the limiting factors of the Tourism Suitability Index Value (IKW). This research was carried out for 1 month, namely from the beginning of March to the beginning of April 2021. The method used in this research was the purposive sampling method. The analysis parameters used are depth, beach type, beach width, bottom water material, current speed, beach slope, water brightness and beach land cover. Based on the results of observations, it shows that the Malaga Beach tourist attraction has good potential because it has a wide sand beach and has not big waves. The research results show that the Tourism Suitability Index (IKW) value is 58.16% and is classified as S3 (Conditionally Suitable) level of suitability. This value provides information that the tourist attraction is in the appropriate category conditionally for the feasibility of its development. The condition for the development in question is the appropriate use of potential, namely the potential width or breadth of the beach as well as the presence of shady pine and palm trees by creating comfortable shelters such as tourist tents, gazebos, children's toys. Thus, Malaga Beach, Siwalu Banua II Village, Gunungsitoli Idanoi District, Gunungsitoli City, North Sumatra has good potential to be developed into a recreational tourism and children's play location, but is not suitable for swimming tourism.